Retrospective study and ongoing investigation of gastric ulceration in flat racing horses in SLTC (Selangor Turf Club) - Kanth, S.; Tan, J. T. (Universiti Putra Malaysia Press, 2004)
A total of 52 horses from the SLTC (Selangor Turf Club) with the complaint of recurrent of colic and reduce performance were gastroscoped. All the horses were aged between 3 to 7 years old and came from the racing field with different working status (rest, training, and racing) at the time of complaint. Majority of the horses were fed mixed feed 3 times a day. From the Study, 45 horses were confirmed to have gastric ulcer of various grades. Treatment was given and reevaluation was done after 21 days. All the horses showed reduction of the ulcer grade.